Cultural Values of Reog Ponorogo and Its Contribution to the Islamization in East Java, Indonesia - Halim, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
Reog Ponorogo dance performance has an entertainment nuances also saves social values and the history of Islamization in Ponorogo. Historical figures such as Suryo Alam, Betoro Katong, Ki Ageng Merah, and Sunan Kalijaga who play a major role in the formation of the value structure of the Reog Ponorogo dance that is reflected in the dance movements. This paper discusses the interpretation of the values contained in Reog Ponorogo both the values of customs, culture, social, politics, and history of the transformation of the life of the old people towards the life of a new society. The method of analysis with Pierre F. Bourdieu’s theory of social action to see that in behavior that is objectified by the Ponorogo community after being observed and conducting in-depth interviews shows that there is a dynamic relationship between the social behavior of the Ponorogo community and the values contained in Reog dance. On the other hand, the history of Ponorogo Islamization can also be read from the Reog Ponorogo dance. In the end, the Reog Ponorogo dance art became an accumulation of values, ranging from history, custom-culture, to social behavior that formed a dynamic, inclusive, and transformative society to openly develop, and always dialectic with the times.